The Relationship Between Breastfeeding Mother's Knowledge and Feeding Exclusive Breastfeeding at PMB A Bogor City - Herawati, Nurul; Munah, Fauzul; Noviana, Ekki; Askar, Nafisah (Jurnal Multidisiplin Indonesia, 2024)
Breast milk (breast milk) is the main and best food at the beginning of a baby's life naturally, without other food additives in babies aged 0-6 months. The Indonesia Health Profile (2018) shows that the proportion of breastfeeding patterns in Indonesia is 37.3%, this figure is still below the target of 80%. The percentage of exclusive breastfeeding in Bogor City in 2019 was 54.7%. In 2020 before, it was 53.15%. In the PMB A work area of Bogor City, the coverage of exclusive breastfeeding is low. Various factors affect the provision of exclusive breastfeeding, including the lack of information and knowledge of mothers about the benefits of exclusive breastfeeding. Research Objective: To find out the relationship between breastfeeding mothers' knowledge and exclusive breastfeeding in PMB A Bogor City. This study uses an analytical descriptive method with a cross-sectional design. The total population is 39 people, with a sample of 36 people. The sampling technique used is purposive sampling. Data were collected using questionnaires. The analysis methods used were univariate test and bivariate test using Chi-square ? = 0.05. Univariate analysis showed that breastfeeding mothers aged 21-30 years (61.1%), high school education (33.3%), and IRT employment (58.3%). Knowledge is lacking (41.7%), and mothers do not breastfeed exclusively (55.6%). The results of the bivocal analysis showed that there was a relationship between maternal knowledge and exclusive breastfeeding (p-value a = 0.004). There is a relationship between maternal knowledge and exclusive breastfeeding in PMB A Bogor City.